Daily field checking list by Walter Rosene, February 16, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, February 16, 1941. Also notes no eggs in an owls nest yet and the old birds have not been seen. Plustek--flatbed